Наказание - смерть: роман / Нора Робертс - Робертс Нора (Моя любовь, 2002)
Экземпляры: ф.9 (2003) / Инвентарный номер: 47447 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: Р 58 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-44